Honeycomb-patterned porous films fabricated via self-organization of Tb complex-loaded amphiphilic copolymers. Issue 35 (29th May 2018) - Liu, Qian; Yan, Chun-Na; Li, Yu-Chao; Li, Mei-Fang; Bai, Li-Ping; Wang, Li-Ping; Li, Guang
Abstract : Amphiphilic copolymers PS- b -Tb complex were synthesized by RAFT polymerization, the honeycomb structured porous films were fabricated via BFM, the hydrophilic groups (Tb complex groups) were mainly distributed at the pore wall. Abstract : Amphiphilic copolymers, poly(styrene)- block -Tb complex (PS- b -Tb complex), were synthesized by reversible addition fragmentation chain transfer (RAFT) polymerization. The honeycomb structured porous films were fabricated via dropping the PS- b -Tb complex copolymer solutions on glass substrates by the breath figures method (BFM). The structure and composition of the amphiphilic copolymer PS- b -Tb complex were confirmed by gel permeation chromatography (GPC), Fourier transform infrared spectroscopy (FT-IR) and 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR). The surface morphology and elemental mapping of the highly ordered porous films were investigated by field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDX) and laser scanning confocal microscopy (LSCM). The results indicated that the solvent type and copolymer concentration can affect the surface morphology of the porous films. The average diameter of the pores in the porous films decreased with the polymer concentration and the molecular weight of the copolymers increased. The FESEM-EDX analysis further verified that the hydrophilic groups (Tb complex groups) were mainly distributed at the pore wall, instead of at the outer surface layer of the films, which was consistent with the LSCM results.